Comparison of NAFLD Fibrosis Score with Shear Wave Elastograpghy to Identify Liver Fibrosis in Patients with NAFLD - Muhammad Azhar Waseem, Sonia Saleem, Muhammad Yasir Younis, Saad Hassan Khan, Sadia Jabbar, Asmat Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: NAFLD is diagnosed by non-invasive and invasive methods. Non-invasive methods include NAFLD fibrosis score, AST/Platelets ratio index (APRI), FIB-4 score, BARD score, USG abdomen, Fibro-scan liver, transient elastography, MRI and MRI with elastography (MRE). Objectives: To determine the frequency of different grades of fibrosis on shear wave elastography in patients with NAFLD and to compare mean NAFLD fibrosis score in different stages of liver fibrosis. Study design: Cross-sectional study. Study duration: 26th February 2021 to 25th August 2021. Settings: Department of Gastroenterology SZH, Lahore. Materials & Methods: A total of 197 patients with NAFLD of age 18-70 years were included. Patients with hepatitis B and/or C infection, hemochromatosis, Wilson’s disease, Alpha 1 antitrypsin deficiency, celiac disease, autoimmune hepatitis, primary biliary cholangitis, primary sclerosing cholangitis were excluded. Hepatic ultrasonographic examination was performed. Blood samples were taken in a 10cc BD syringe and were sent for assessment of PT/INR, LFTs including albumin, platelets count and fasting or random glucose level. Reports were assessed and the NAFLD fibrosis scores were calculated. Shearwave elastography was used as gold standard test for the detection and confirmation of liver fibrosis; and results were compared. Results: Age range in this study was from 18 to 70 years with mean age of 49.30 ± 12.05 years. Majority of the patients 145 (73.60%) were between 41 to 70 years of age. Out of these 197 patients, 80 (40.61%) were males and 117 (59.39%) were females with male to female ratio of 1:1.5. In this study, frequency of different grades of fibrosis on shear wave elastography in patients with NAFLD was as follows; F0 in 44 (22.34%), F1 in 89 (45.18%), F2 in 31 (15.74%), F3 in 22 (11.17%) and F4 in 11 (5.58%) patients. Conclusion: This study concluded that non-invasive NAFLD fibrosis score should be used to rule out the presence or absence of liver fibrosis by using simple clinical and biochemical variables and thus avoid the need of liver biopsy.